Normas tributárias indutoras na concretização do princípio constitucional da redução das desigualdades sociais e regionais - Cabral, Indhira de Almeida (2008)
The Federal Constitution states that the reduction of social and regional inequalities is one of the goals to be achieved by the Brasilian State. The economic constitution states that the national economy must be developed so as to achieve, amongst other objectives, the reduction of those inequalities. In this paper, we aim to demonstrate the duty, imposed by the Constitution to the State, of acting in the national economy so as to promote the achievement of the constitutional goals, among wich we highlight the reduction of inequalities. One of the instruments that can be used by the State to achieve this objective is its fiscal policy. It is also an aim in this paper to demonstrate that inducing tax norms can be used by the State, because it can encourage the economic agents to bring about the reduction of social and regional inequalities. Therefore, after bibliographic and jurisprudential research, we conclude that the duty, imposed to the State, of acting in the national economy so as to promote the achievement of the constitutional goals exists. We also conclude that this acting must be planed and constant, because the consequences are slow and that, within the limits of the constitution, the inducing tax norms can be an instrument for the State in order to reduct the social and regional inequalities